2009
DOI: 10.1016/j.physleta.2009.07.032
|View full text |Cite
|
Sign up to set email alerts
|

Self-organization of quasi-equilibrium steady-state condensation in accumulative ion-plasma devices

Abstract: We consider both theoretically and experimentally self-organization process of quasi-equilibrium steadystate condensation of sputtered substance in accumulative ion-plasma devices. It has been shown that the self-organization effect is caused by self-consistent variations of the condensate temperature and the supersaturation of depositing atoms. Two possible types of self-organization process have been found out on the basis of the phase-plane method. The aluminium condensation experimental data confirming the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 15 publications
1
16
0
8
Order By: Relevance
“…Our previous works [37][38][39][40] have shown that, self-assembling of ordered nanoparticles system or nanoporous structures can be implemented under near-equilibrium condensation conditions in the plasma-condensate system. It has been established, that the nucleation occurs only on the limited amount of active centers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous works [37][38][39][40] have shown that, self-assembling of ordered nanoparticles system or nanoporous structures can be implemented under near-equilibrium condensation conditions in the plasma-condensate system. It has been established, that the nucleation occurs only on the limited amount of active centers.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the free energy minimization together with Ostwald ripening determine the monodispersity of the nanoparticles shape and size on the nucleation stage [41][42][43][44]. The more prolonged condensation results in the porous structures growth which is caused by an incomplete intergrowth of newly formed nanoparticles [45,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The above‐described non‐linear interdependence of the deposition parameters stabilizes the supersaturation value at a constant level. The mathematical model of self‐organization of small steady‐state supersaturations in APCS is described in detail in .…”
Section: Methodsmentioning
confidence: 99%